The American nation : - Garraty, John Arthur (Longman, 1998)
This volume is a comprehensive political history of the American nation which integrates social, economic and cultural developments in a single treatment. This edition has been updated to include Newt Gingrich's Contract with America, the 1996 election and the 1995 budget crisis.